Improving Lactation Education and Support in Primary Care. Issue 5 (September 2021) - Spatz, Diane L.
Abstract : Nurses in pediatric and primary care practices that offer well-baby outpatient visits must know about the technical aspects of breastfeeding, the science of human milk and the physiology of lactation so they can support breastfeeding families to reach their personal breastfeeding goals. Our breastfeeding expert, Dr. Spatz, offers suggestions for incorporating lactation care into pediatric and primary care practices.